IMF Survey, Volume 37, Issue 03. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
Global Imbalances, Africa's Improved Debt Outlook, Nigerian Reform, Burkina Faso's Cotton Crisis, Ghana and Inflation Targeting, Iraq's Progress, Egypt's Reforms Spur Growth, Asian Trade, Baltics' High Growth Rate, News Briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet